Studies on the scab disease of apples caused by Venturia inaequalis (Cke.) Wint. with particular reference to its epiphytology and control in the winter rainfall area of the Cape Province - Louw, A. J.(Adriaan Jacobus) (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Sc. (Agric.)) -- University of Stellenbosch, 1946.